The Effectiveness of Science Laboratory Course Regarding the Scientific Process Skills and Scientific Creativity of Prospective Teachers - Esin ŞAHİN-PEKMEZ; Hilal AKTAMIŞ; Bilge CAN (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
In this research, primary science and mathematics prospective teachers’ scientific process skills and scientific creativity levels have been determined in science laboratory course. The research sample covers 84 primary science and mathematics prospective teachers. The content of the course includes some science scenarios which require the use of samples’ scientific creativity and critical thinking. In the light of these scenarios, the teacher candidates were required to design an experiment and then using their scientific process skills carry out the experiment. According to their written accounts student teachers abilities of scientific creativity and using scientific process skills were measured. As a result it was found out that, prospective teachers’ scientific process skills in both departments are at a good level and there is a significant difference in favor of mathematics prospective teachers. However, there is not a significant difference in terms of scientific creativity of the mathematics and science prospective teachers.